White-light speckle image correlation applied to large-strain material characterization - Broggiato, Giovanni B.; Cortese, Luca (European Journal of Computational Mechanics, 2009)
In experimental mechanics, the possibility of tracking on component surfaces the full-field stress and strain states during deformation can be utilized for many purposes such as formability limits determination, quantification of stress intensification factors, material characterization and so on. Concerning the last topic, an interesting application could be a direct identification of the elasto-plastic material response up to large deformation. It is well known, in fact, that with traditional measurement devices it is possible to retrieve the true equivalent stress versus true equivalent strain data from tensile tests only up to the onset of necking, where localization starts to occur. This work aims to show how from the knowledge of a tensile test full-field strain and of load data it will be possible to obtain the full-stress field as well as the complete material elasto-plastic behavior.